Impact of Human Resource Development Programs (HRDP) on Library Staff Productivity in University Libraries in Sokoto State, Nigeria - Saleh, Idris Ibrahim; Yusuf, Suleiman Adamu (Communicate: Journal of Library and Information Science, 2023)
This study investigated the impact of human resource development programmes on library staff productivity in academic libraries in Sokoto State. The survey research design was adopted for this research work and structured questionnaire was used as the instrument for data collection. Out of the total copies of questionnaire administered, 111 were completed and returned and the total numbers of valid questionnaire were 105. Frequencies and percentages were used for analysis. The result of the study showed that human resource development programmes have significantly impacted on the productivity of staff in academic libraries in Sokoto State. The findings also established that the factors that facilitate human resource development makes staff performance, development and productivity process more effective. This study therefore recommends that library management should put in place ways to enforce human resource development policy to strengthen human resource development programmes practice among library staff for optimal performance. Furthermore, the research recommends that library staff should constantly be encouraged to participate and engage in developmental programmes organized within and outside their institutions to ensure increased productivity.